Information Literacy In The Changing Media Environment: The Evolution of Information Literacy Concepts And Practices And Role Of Libraries In Education And Life-Long Learning - Surattee, Idris Rashid Khan (2015)
The proliferation of digital news media and social media in the last 10 years is transforming the nature of news content. The emergence of participatory social media is redefining the relationship between newsroom and consumers of news and media information. Media literacy, which emerged out of the social critique of mass media with emphasis on deconstruction of media messages, is now focusing on competencies for participatory culture in the new media. Over the years information literacy, media literacy, and critical literacy have developed independently of each other, championed by different professions and focusing on different core competencies and learning outcome. Convergence of elements in the media industry, information services and educational pratices, requires the convergence of various concepts of literacy in developing new competencies for life-long learning. This paper will briefly discuss the silent features, of the three literacy concepts and pratices, namely information literacy, media literacy and critical literacy, which evolved out of different fields of practice.